PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PT. MATAHARI CIPTA SENTOSA - Pranata, Agustinus; Karnadi, Karnadi; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Human resources are one of the resources contained in the organization, including all people who carry out activities. An employee who gets job satisfaction from his job will maintain high work performance. The purpose of this study was to analyze and test the effect of the work environment on employee performance through job satisfaction as an intervention variable. The population in this study were employees of PT. Matahari Cipta Sentosa. The sampling technique was determined by saturated sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, work environment has a significant positive effect on job satisfaction, work environment has a significant positive effect on performance, job satisfaction has a significant positive effect on performance. The results of the indirect effect hypothesis test show that the work environment variable on performance through job satisfaction has a significant positive effect.